Online backchannel as a formative assessment in improving writing skills - Entika Fani Prastikawati; Wiyaka Wiyaka; AB Prabowo Kusumo Adi (Institut Agama Islam Negeri (IAIN) Palangka Raya, Indonesia, 2020)
Technology integration in language assessment has been regarded as a common strategy in an educational setting. However, teachers need to adjust the perception and cogency of assessment in an online setting as well as the concept of formative assessment in online environments. This research aimed to investigate the students' perception of online backchannel implementation as a formative assessment in improving the students' writing skills in an English classroom. For this purpose, a mixed-method was applied with a closed-ended questionnaire distributed to 32 students and semi-structured interviews carried out to 24 students at the eighth-grade students of a state junior high school in Semarang, Central Java, Indonesia. The collected data were then analyzed quantitatively using SPSS 23 and qualitatively. The findings revealed positive perceptions of online backchannel implementation as a formative assessment in improving their writing skills. They considered it a new and innovative process of an assessment that helped them get the maximum result of writing. Furthermore, students' motivation and confidence in writing were raised. This study's implication calls for the implementation of online backchannel in English class as a formative assessment during the writing process.